2001
DOI: 10.1097/00001756-200108080-00029
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the functional anatomy of empathy and forgiveness

Abstract: Previous functional brain imaging studies suggest that the ability to infer the intentions and mental states of others (social cognition) is mediated by medial prefrontal cortex. Little is known about the anatomy of empathy and forgiveness. We used functional MRI to detect brain regions engaged by judging others' emotional states and the forgivability of their crimes. Ten volunteers read and made judgements based on social scenarios and a high level baseline task (social reasoning). Both empathic and forgivabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
157
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(174 citation statements)
references
References 22 publications
12
157
0
2
Order By: Relevance
“…58 This broad functionality underlines the role of the precuneus in many highly integrated mental functions that are not limited to simple visuospatial processing. This assumption is supported by fMRI studies investigating social cognition 62 and emotional state attribution. 63 Therefore, previous research with regard to anatomic connectivity has helped to clarify the nature of structural reductions of the orbitofrontal cortex in depressed patients and the association with increased cerebral activity in the reported structures in the context of emotional processing.…”
Section: Discussionmentioning
confidence: 74%
“…58 This broad functionality underlines the role of the precuneus in many highly integrated mental functions that are not limited to simple visuospatial processing. This assumption is supported by fMRI studies investigating social cognition 62 and emotional state attribution. 63 Therefore, previous research with regard to anatomic connectivity has helped to clarify the nature of structural reductions of the orbitofrontal cortex in depressed patients and the association with increased cerebral activity in the reported structures in the context of emotional processing.…”
Section: Discussionmentioning
confidence: 74%
“…This activation was observed in prior studies of moral reasoning and was specifically associated with evaluating the appropriateness of solutions to personal moral dilemmas (Greene et al, 2001). The posterior cingulate cortex has been implicated in seemingly diverse functions including the experience of emotion (Mayberg et al, 1999), recall of emotional memories (Maratos, Dolan, Morris, Henson, & Rugg, 2001;Maddock, Garrett, & Buonocore, 2003), reward processing (Knutson et al, 2003), forgivability (Farrow et al, 2001), and self-reference (Fossati et al, 2003, Johnson et al, 2002and Kelley et al, 2002Ruby and Decety, 2003). The posterior cingulate cortex is also activated by the successful recall of autobiographical memories (Maddock, Garrett, & Buonocore, 2001;Piefke, Weiss, Zilles, Markowitsch, & Fink, 2003).…”
Section: Dorsal Posterior Cingulate Cortexmentioning
confidence: 69%
“…Macaskill, Maltby, and Day (2002) reported a relationship between empathy and forgiveness of others but not oneself. Farrow et al (2001) even showed common neurophysiological correlates of empathy and forgiveness. In sum, multiple forms of evidence point to a link between empathy and forgiveness.…”
Section: Empathy and Forgivenessmentioning
confidence: 98%